Value relevance of financial risk disclosures - Arlindo Menezes da Costa Neto; Atelmo Ferreira de Oliveira; Aline Moura Costa da Silva; Alexandro Barbosa (Journal of Capital Markets Studies (JCMS), 2023)
Purpose - The objective of the present study is to examine the value relevance of accounting information presented by Brazilian banks. Design/methodology/approach - The studied sample derived from Brazil's Stock Exchange, B3, under the banking segment, resulting in a group of 24 publicly listed companies, whose data ranged from 2017 to 2019. The study was conducted using the disclosure index, made with the intent of evaluating the disclosure adherence of a company to the reporting standard. In this case, Comitê de Pronunciamentos Contábeis (CPC) 40, financial instruments: recognition, evaluation and disclosure, Instrumentos Financeiros: Evidenciaç\~ao, Brazil's interpretation of the International Financial Reporting Standards (IFRS) 7. Findings - The results show that for the sample and period, the disclosure index cannot be used as an explanatory variable for the market evaluation of financial institutions. Originality/value - While other studies have presented a similar approach to the value-relevance theme, the present work is original as it develops the methodology on financial institutions, and even more so on the financial institutions of a developing country.
Keywords: 330; Financial instruments; IFRS 7; Risk disclosure; Value relevance